TANGGUNG JAWAB PELAKU USAHA TERHADAP RISIKO KECACATAN PRODUK BAGI KONSUMEN MOBIL LISTRIK DENGAN FITUR KENDALI OTOMATIS (SELF-DRIVING) BERDASARKAN UNDANG-UNDANG NOMOR 8 TAHUN 1999 TENTANG PERLINDUNGAN KONSUMEN - Atrina Isti Oilinda; Andi Muhammad Rusdi (Fakultas Hukum Universitas Borobudur, 2024)
Presence of automatic control features in current transportation, especially passenger cars, will significantly impact the necessary preparations. Automatic control features can operate the vehicle, commonly known as selfdriving. When defects in these features cause accidents, the responsible business entities are obligated to compensate for resulting losses to protect consumers. The issue addressed in this research is the responsibility of businesses and other related parties in cases of defects in electric vehicleswith automatic control features, and the legal remedies available to Indonesian consumers experiencing losses due to such defects. The research methodology employed is normative juridical. In this context, businesses must compensate consumers for losses, involving liability based on breach of contract and unlawful acts, and pursuing legal action persuasively through litigation or alternative dispute resolution methods such as mediation, conciliation, and arbitration via consumer dispute resolution bodies.